Improved space‐vector modulation technique for common mode currents reduction. Issue 7 (1st August 2013) - Cacciato, Mario; De Caro, Salvatore; Scarcella, Giuseppe; Scelba, Giacomo; Testa, Antonio
Abstract : Modified space‐vector modulations (MSVMs) that reduce the variations of common mode voltage (CMV) for decreasing common mode currents (CMCs) are a low cost interesting approach. Unfortunately the lack of full utilisation of the DC bus voltage is a severe drawback that can limit the exploitation of such modulation techniques, unless special overmodulation methods are adopted. In this study, some solutions are presented that make a trade‐off between the DC bus voltage exploitation and CMCs reduction and make MSVMs appealing to most electrical drives on the market. Furthermore, the influence of dead time in CMV generation is considered thus modifying the switching patterns according to the sign of the load currents. Experimental results are presented in order to confirm the feasibility of the proposed approach.